Ruang Terbuka Hijau; Landsat 8 O Analisis Ketersediaan Ruang Terbuka Hijau Dengan Metode Normal Difference Vegetation Index Menggunakan Citra Landsat 8 - Hanhan Mohammad Ramdan (JURNAL GEOGRAFI, 2021)
The increasing number of residents in urban areas has an impact on urban management, especially in the aspect of providing green open space (RTH). This indicates the need to stimulate the availability of green open space both in terms of quality and quantity. The development of industrial areas is an attraction for workers both from within and outside the city of Bandung. The aim of this research is to determine the availability of green open space in the city of Bandung. This research uses data from Landsat 8 OLI satellite imagery. The method used in this study was carried out throughout the city of Bandung with digital image interpretation methods. The result shows that the Change in Availability of Green Open Space (RTH) in the Bandung City area in 2019 is considered quite stable. So that the area of ​​green open space in the city of Bandung in the same year was only 15% of the entire area of ​​​​the city of Bandung.